2014
DOI: 10.1245/s10434-014-3799-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Patient Outcome of Melanoma Nodal Metastases and an Unknown Primary Site

Abstract: BackgroundMelanoma of unknown primary site (MUP) is not a completely understood entity with nodal metastases as the most common first clinical manifestation. The aim of this multicentric study was to assess frequency and type of oncogenic BRAF/NRAS/KIT mutations in MUP with clinically detected nodal metastases in relation to clinicopathologic features and outcome. Materials and MethodsWe analyzed series of 103 MUP patients (period: 1992–2010) after therapeutic lymphadenectomy (LND): 40 axillary, 47 groin, 16 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
1
13
0
3
Order By: Relevance
“…Two thirds of the participants estimated that the skin was the most likely primary site for MUP, in agreement with recent studies demonstrating a similar molecular profile between MUP and melanomas on nonchronically sun-damaged skin [16,17] .…”
Section: Discussionsupporting
confidence: 89%
“…Two thirds of the participants estimated that the skin was the most likely primary site for MUP, in agreement with recent studies demonstrating a similar molecular profile between MUP and melanomas on nonchronically sun-damaged skin [16,17] .…”
Section: Discussionsupporting
confidence: 89%
“…Although there are no specific treatment recommendations for patients with MUP, physicians tend to apply similar strategies for patients with stage‐matched MKP . This approach is supported by the results of a large study into the molecular characterisation of patients diagnosed with MUP, in which it was shown that the clinical behaviours and molecular patterns of BRAF/NRAS alterations were similar between patients with MUP and stage‐matched MKP …”
Section: Discussionmentioning
confidence: 96%
“…20 This approach is supported by the results of a large study into the molecular characterisation of patients diagnosed with MUP, in which it was shown that the clinical behaviours and molecular patterns of BRAF/NRAS alterations were similar between patients with MUP and stage-matched MKP. 21 The percentage of Dutch patients diagnosed with stage IV MUP who were primarily treated with novel therapy increased considerably during the study period. Consistent with the respective approval dates, targeted therapies (approved 2012-2015) were prescribed at higher rates early in the novel therapy era, whereas immunotherapies were prescribed at higher rates later in that era (approved 2011 and 2015-2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ved klinisk undersøkelse ble det funnet en palpabel knute i venstre lyske. Orienterende blodprøver viste senkning 23 mm (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), forhøyet CK 810 U/l (35-210), troponin T 134 ng/l (< 14), LD 294 U/l (105-205) samt negativ revmatoid faktor og antisykliske citrullinerte peptider. ANA var positiv (> 160), med negative undergrupper, inklusive myositt-og sklerodermaspesifikke antistoffer og de malignitetsassosierte antistoffene RNA-polymerase III, TIF1-γ og NXP-2.…”
Section: Figur 2 A) Kapillaroskopi Av Negleseng Hos Frisk Person Med unclassified
“…Det ble ikke sett tegn til arytmi ved 24 timers EKG eller ved fem dagers EKG-registrering. Orienterende blodprøver viste hemoglobin 12,9 g/dl (11,(7)(8)(9)(10)(11)(12)(13)(14)(15)3), senkning 26 mm (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). C-reaktivt protein, trombocytter og leukocytter var innen gjeldende referanseområder.…”
unclassified